PENGARUH KINETIC SAND TERHADAP KETERAMPILAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK ISLAM RIADHUSSOLIHIN KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Anissa Anissa; Zulkifli N Zulkifli N; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to examine the effect of kinetic sand on fine motor skills in children age 4-5 years.This research is conducted at TK Islam Riadhushholihin, Subdistrict of Rambah during January 2018. The research used experimental method that was one group pre-test post-test design with 20 children as the sample. The instrument type witch is used in this study is observation and documentation. Spss 17 is used for the data analysis techniques. Based on the result of the hypothesis that there is an effect of kinetic sand on fine motor skills on children aged 4-5 years at TK Islam Riadhussolihin, Subdistrict Rambah. Obtained t-count value is 23,126 with sig 0,000, because sig <0,05 hence can be concluded that there is influence of kinetic sand on fine motor skills on children. In Hypothesis test can be seen t-count = 23,126 > ttabel = 2,093. It can be interpreted that there is a significant influence of kinetic sand on fine motor skills on children aged 4-5 years at TK Islam Riadhussholihin, Subdistrict Rambah of 48,28%.Key words: fine motor skills , kinetic sand